An online tool for predicting ovarian reserve based on AMH level and age: A retrospective cohort study - Han, Yong; Xu, Huiyu; Feng, Guoshuang; Wang, Haiyan; Alpadi, Kannan; Chen, Lixue; Zhang, Mengqian; Li, Rong (Frontiers in Endocrinology, 2022)
Purpose To establish a more convenient ovarian reserve model with anti-Müllerian hormone (AMH) level and age (the AA model), with blood samples taken at any time in the menstrual cycle. Methods We have established this AA model for predicting ovarian reserve using the AMH level and age. The outcome variable was defined as poor ovarian response (POR) with <5 oocytes retrieved during assisted reproductive technology treatment cycles. Least Absolute Shrinkage and Selection Operator logistic regression with 5-fold cross validation methods was applied to construct the model, and that with the lowest scaled log-likelihood was selected as the final one. Results The areas under the receiver operating characteristic curve for the training, inner, and external validation sets were 0.862, 0.843, and 0.854 respectively. The main effects of AMH level and age contributing to the prediction of POR were 95.3% and 1.8%, respectively. The incidences of POR increased with its predicted probability in both the model building and in external validation datasets, indicating its stability. An online website-based tool for assessing the score of ovarian reserve (http://121.43.113.123:9999) has been developed. Conclusions Based on external validation data, the AA model performed well in predicting POR, and was more cost-effective and convenient than our previous published models.